Management of the development of academic activities through the use of ICT by Huánuco university students - Portocarrero-Veramendi, Ewer R. (2020)
The present study aimed to determine the relationship between the management of the development of academic activities and the use of ICT by Huánuco university students. Methods. The study was of a quantitative approach, descriptive type with correlational design, with a sample selected by stratified probabilistic sampling method made up of 245 students from the Faculties of Education, Administration and Nursing of a public university in Huánuco. For data collection, the survey technique was used, the instruments of which were the learning management measurement questionnaire and the questionnaire for measuring the frequency and amplitude of the use of ICT, which were previously validated and reliable. Descriptive analysis was performed and the hypotheses were tested using Pearson's X2 test. The ethical considerations of the research were applied. Results. It was observed that 62.9% (154) of the university students used ICT at the medium level, 22% (54) at the high level and 15.1% (37) at the low level. Regarding the description of the management of the development of academic activities, the majority expressed a regular level [73.1% (179)], 17.1% (42) an optimal level and 9.8% (24] a deficient level. Conclusion. the existence of a relationship between the management of the development of academic activities and the use of ICT, by university students from Huánuco, 2019 (X2 = 178.752 for 4 degrees of freedom and p = 0.000).